The Influence Of Students’ Creative Thingking Ability And Achievement Motivation On Vocational School Students’ Learning Outcomes - Ferry Indra Sakti H Sinaga; Frida Marta Argareta Simorangkir (Journal on Education, 2024)
One of the objectives of vocational school education is to produce graduates who have adequate competence as indicated by the achievement of good learning achievement indicators. To get good learning achievement is influenced by many factors, including students' creative thinking ability and achievement motivation. From the results of this study using multiple regression analysis, it was found that the regression equation was Y = 6.929 + 0.053 X1 + 0.110 X2. Creative thinking ability and achievement motivation have a positive relationship with student learning outcomes. In other words, to improve student learning outcomes, students must have high creative thinking skills and high achievement motivation as well.